Effectiveness of Massage Therapy for Treatment of Infantile Colic - Munazza Saleem,. Javeria Bhatti, Matloob Azam (Journal of Rawalpindi Medical College, 2013)
Background: To compare modes of administration of massage therapy for management of infantile colic. Methods: This prospective study included exclusively breast fed infants less than 4 months of age and diagnosed as cases of infantile colic. Patients were randomly assigned to receive a standard massage either during colic episode (group A) or as daily care (group B) or no intervention at all (group C). Change in mean duration of crying (minutes/day) was primary outcome while weight gain and number of patients showing 50% reduction in crying time were secondary out comes. Results: A significant reduction of crying time was observed only in group A compared to other two groups (p<0.005) on day 7, 14 and 21 of therapy. Majority of patients (90.3%) in group A showed 50% reduction in basal crying time. Patients in group A showed better weight gain compared to group B and group C but this was not significant (p value= 0.385). Conclusion: Massage therapy is better than no intervention for colic.